Sistem Keuangan Islam dan Konvensional: Sebuah Studi Literatur - Asmaul Husna; Julfan Saputra; M. Shabri A. Majid; Marliyah; Rita Handayani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
The Islamic Financial System is an implementation of the teachings of Islamic economics. So, the values contained in Islamic teachings must be realized in the Islamic financial system. But in reality, many criticisms are related to the Islamic financial system. This paper is a literature review that aims to determine the Islamic and conventional financial systems. This research uses an approach using Publish and Perish software to collect journal articles that are relevant to the purpose of this research. The contents of the collected articles were analyzed to get a conclusion. The main findings of this study indicate that the orientation of the Islamic financial system is profit and falah oriented while the conventional financial system is only profit-oriented, the conventional financial system must pay attention to the principle of justice in its operations so as not to harm the community.